Lipid-Based Nutrient Supplements Plus Malaria and Diarrhea Treatment Increase Infant Development Scores in a Cluster-Randomized Trial in Burkina Faso. Issue 4 (9th March 2016) - Prado, Elizabeth L; Abbeddou, Souheila; Yakes Jimenez, Elizabeth; Somé, Jérôme W; Ouédraogo, Zinewendé P; Vosti, Steve A; Dewey, Kathryn G; Brown, Kenneth H; Hess, Sonja Y; Ouédraogo, Jean-Bosco
Abstract: Background: Adequate nutrition is necessary for the rapid brain development that occurs during infancy. Objectives: We tested the hypothesis that the provision of small-quantity, lipid-based nutrient supplements (SQ-LNSs) plus malaria and diarrhea treatment positively affects infant development. We also tested the effect of various doses of zinc provided in SQ-LNSs or in a tablet. Methods: In a partially masked, cluster-randomized controlled trial, communities in rural Burkina Faso were stratified by selected characteristics and then randomly assigned within strata to the intervention (IC; 25 communities, 2435 children) or the nonintervention (NIC; 9 communities, 785 children) cohorts. IC children were randomly assigned to 4 groups. As secondary outcomes, a subsample of 3 of these 4 groups ( n = 747) and of the NIC ( n = 376) were assessed for motor, language, and personal-social development at age 18 mo by using the Developmental Milestones Checklist II. The 3 IC groups received 20 g SQ-LNSs/d containing 0 or 10 mg added zinc with a placebo tablet or 20 g SQ-LNSs/d containing 0 mg added zinc with a tablet containing 5 mg Zn. All IC groups received treatment of malaria and diarrhea from age 9 to 18 mo. Data collectors and participants were aware of allocation to the IC or NIC but did not know the particular IC subgroup. Results: Children in the IC scored 0.34 (95% CI: 0.21, 0.46), 0.30 (95% CI: 0.15, 0.44), and 0.32 (95% CI: 0.16, 0.48) SDs higher in motor, language, and personal-social development, respectively, than did children in the NIC (All P < 0.001). Children who received different amounts of zinc did not differ significantly in any of the scores. No effect on caregiver-child interaction was found. Conclusion: In rural Burkina Faso, the provision of SQ-LNSs to infants from age 9 to 18 mo, regardless of added zinc content, plus malaria and diarrhea treatment positively affected motor, language, and personal-social development at age 18 mo. This trial was registered at clinicaltrials.gov as NCT00944281.